Reliability of PWB microvias for high density package assembly. (16th July 2008) - Ghaffarian, Reza
High density PWB (printed wiring board) with microvia technology is required for implementation of high density and high I/O area array packages (AAP). COTS (commercial off-the-shelf) AAP packaging technologies in high reliability versions with 1.27 mm pitch are now being considered for use in a number of NASA systems including Space Shuttle and Mars Rovers. NASA functional system designs are requiring more and more dense AAP packages and board space, which makes board microvia technology very attractive for effectively routing a large number of package inputs/outputs. However, the reliability of the fine feature microvias including via in pads is unknown for space applications. Understanding process and QA (quality assurance) indicators for reliability are important for low risk insertion of these newly available packages and PWBs. This paper presents literature search as well as test results for a high density board subjected to various thermal cycle and reflow profiles representative of tin-lead and lead-free solder reflow. Microvias sizes ranged from two to six mil with and without filling. Daisy chain microvias monitored during the test and PWBs were cross-sectioned to determine failure and locations. Optical and SEM photographs as well as resistance changes during cycling and Tg/Td (glass transition/decomposition temperature) characterisations are presented.